Biomimetic construction of hierarchical MXene@PDA@CoFeOx nanohybrids towards efficient fire-safe epoxy nanocomposites with enhanced thermal conductivity and mechanical properties - Lian, Richeng; Jiang, Yunpeng; Guan, Haocun; Cui, Jiahui; Gao, Qingyao; Liu, Lei; Chen, Xilei; Jiao, Chuanmei (Polymer degradation and stability, 2023)
•A hierarchical MXene@PDA@CoFeOx has been constructed by a biomimetic strategy.•MXene@PDA@CoFeOx allows EP to easily achieve a UL-94 V0 rating.•MXene@PDA@CoFeOx endows EP with efficient flame retardancy and smoke suppression.•MXene@PDA@CoFeOx improves the thermal conductivity and mechanical performance of EP. Developing high-performance MXene-based polymer nanocomposites through a biomimetic method has been a research hotspot. However, it is still an intractable challenge to achieve MXene-based polymer nanocomposites with efficient fire safety, excellent thermal conductivity, and enhanced mechanical properties. Here, inspired by the adhesion of mussels, the hierarchical MXene@PDA@CoFeOx nanohybrid was fabricated by a self-assembly strategy and then employed to prepare epoxy resin (EP) nanocomposites. It has been found that MXene@PDA@CoFeOx can display excellent dispersion and interfacial compatibility in EP matrix. Thermogravimetric analysis shows that only 2.0 wt% MXene@PDA@CoFeOx results in excellent thermal stability and char yield (31.29 wt%) of EP under a nitrogen atmosphere. Combustion tests show that the 2.0 wt% MXene@PDA@CoFeOx confers efficient fire safety to EP. Remarkably, the EP-2.0%MXene@PDA@CoFeOx can obtain an attractive UL-94 rating of V0. Meanwhile, the peak heat release rate (pHRR), smoke factor (SF), and peak CO production rate (pCO) of EP-2.0%MXene@PDA@CoFeOx are dramatically decreased by 33.38%, 55.41%, and 36.84% in comparison to those of virgin EP, respectively. The efficient fire safety of EP nanocomposites is mainly attributed to the barrier effect, dilution effect, and catalytic carbonization effect of hierarchical MXene@PDA@CoFeOx. Furthermore, the MXene@PDA@CoFeOx enables EP to boast enhanced thermal conductivity (improved by 69.14%), impact strength (improved by 13.38%), and flexural strength (improved by 17.60%). This work offers a feasible biomimetic method for fabricating hierarchical MXene@PDA@CoFeOx nanohybrids and preparing efficient fire-safe EP nanocomposites with excellent thermal conductivity and mechanical performance. [Display omitted]